Analgesic effects of novel lysophosphatidic acid receptor 5 antagonist AS2717638 in rodents. (November 2017) - Murai, Nobuhito; Hiyama, Hideki; Kiso, Tetsuo; Sekizawa, Toshihiro; Watabiki, Tomonari; Oka, Hiromasa; Aoki, Toshiaki
Abstract: Lysophosphatidic acid (LPA) is a bioactive lipid that acts via at least six G protein-coupled receptors, LPA receptors 1–6 (LPA1-6), for various physiological functions. We examined (1) whether LPA5 is involved in pain signaling in the spinal cord; and (2) the pharmacological effects of a novel LPA5 antagonist on intrathecal prostaglandin (PG)- and ( S )-α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA)-induced allodynia, and neuropathic and inflammatory pain in rodents. Intrathecal injection of a selective LPA5 agonist, geranylgeranyl diphosphate, and a non-selective agonist, LPA, induced allodynia in wild type, but not in LPA5 knockout mice. These novel results suggest that LPA5 is important for pain signal transmission in the spinal cord. AS2717638 (6, 7-dimethoxy-2-(5-methyl-1, 2-benzoxazol-3-yl)-4-(piperidin-1-ylcarbonyl)isoquinolin-1(2 H )-one) bound to the LPA-binding site on LPA5 and selectively inhibited LPA-induced cyclic adenosine monophosphate accumulation in human LPA5-but not LPA1-, 2-, or 3-expressing cells. Further, oral administration of AS2717638 inhibited LPA5 agonist-induced allodynia in mice. AS2717638 also significantly improved PGE2 -, PGF2α -, and AMPA-induced allodynia, while both pregabalin and duloxetine alleviated only PGE2 -induced allodynia in mice. Similarly, AS2717638 significantly ameliorated static mechanical allodynia and thermal hyperalgesia in rat models of chronic constriction injury (CCI)-induced neuropathic pain. AS2717638 also showed analgesic effects in a rat model of inflammatory pain. These findings suggest that LPA5 antagonists elicit broad analgesic effects against both neuropathic and inflammatory pain. Accordingly, pharmacological LPA5 antagonists are attractive development candidates for potential novel pain therapies. Highlights: Lysophosphatidic acid receptor 5 (LPA5) is involved in spinal pain signaling. A novel LPA5 antagonist shows broad analgesic effects in multiple animal pain models. Pharmacological antagonism of LPA5 is an attractive novel pain therapy.